PERLINDUNGAN KONSUMEN DARI JERAT KRIMINALISASI UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK: STUDI KASUS PUTUSAN NOMOR 658/PID.SUS/2021/PN SBY - Nanda Wijayanto; Nynda Fatmawati Octarina (Gapenas Publisher, 2023)
The establishment of a Joint Decree on Guidelines for the Implementation of Certain Articles in the ITE Law (SKB Implementation of the ITE Law) was carried out by the government in order to provide legal certainty to people who have been criminalized using the ITE Law instruments. Consumers are one of the parties who experience criminalization under the ITE Law even though consumers have rights regulated in the Consumer Protection Act. The case experienced by Stella Monica is one of the latest examples where judges recognize the principle of legal protection for consumers so that consumers cannot be punished by business actors. The purpose of this research is to find out the ratio decicdendi in Decision Number 658/Pid.Sus/2021/Pn.Sby so that giving an acquittal to the defendant is in accordance with the theory of consumer protection and whether the Joint Decree on the Implementation of the ITE Law can be used as a preventive measure against consumer protection from threat of action under Article 27 Paragraph (3) of the ITE Law concerning the Crime of Defamation?. The research method used is normative juridical research with statutory and case approaches. The results of the study show that the acquittal received by Stella is in accordance with the principles of consumer protection. The judge's consideration stated that Stella's actions which were the demands of the public prosecutor were a complaint, not as a defamation. The action of